Asas Umum Pemerintahan Yang Baik Berlandaskan Pancasila Sebagai Dasar Penggunaan Diskresi - Muhammad Aziz Zaelani; I Gusti Ketut Ayu Rachmi Handayani; Isharyanto Isharyanto (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This study aims to answer two problems: first, classifying and describing the antinomy of discretionary regulation in Law No. 30 of 2014 concerning Government Administration; and secondly, carrying out the construction on AUPB that has been filtered with Pancasila. Antinomy is the root of the conflict between freedom and responsibility. In this paper, antinomy is used as a way of thinking to examine the legality of limiting discretion. This is a doctrinal legal research. The sources information used in the study are primary legal materials (relevant regulations and documents) to be further analysed in a qualitative manner. Conceptual, historical and comparative law approaches are used to help solve problem formulations. The results showed that first, the antinomy that is governed under Law No. 30 of 2014 is irrelevant to the rule of law principles, thus creating confusion in the praxis realm of of the government; Second, the construction of a regulation is needed to formulate AUPB based on Pancasila as the basis for regulating discretion.